Pesona Kekayaan Alam: Sumber Konflik di Kawasan Laut China Selatan - Auliah Ambarwati; Adi Prahmana Putra; Ahmad Wadil Aryadi; Nabila Nabila; Nurriskayanti Ramli; Arzety Najwa; Sutriani Sutriani (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2023)
This research paper examines the influence of natural resources on international conflicts, focusing on the case study of the South China Sea dispute. The South China Sea is an area rich in natural resources, including oil, gas, and fisheries, which has resulted in competing territorial claims among several countries in the region. The objective of this study is to analyze the relationship between natural resources and the escalation of conflicts in the South China Sea. The findings suggest that the abundance of natural resources in the South China Sea has significantly contributed to the escalation of conflicts in the region. The competition for energy resources, fisheries, and strategic control has intensified rivalries and territorial disputes among the claimant states. The findings of this study contribute to the existing body of knowledge on the relationship between natural resources and international conflicts and provide insights into the challenges and potential avenues for peaceful resolution in the South China Sea